2020
DOI: 10.32641/rchped.v91i3.1167
|View full text |Cite
|
Sign up to set email alerts
|

Extubación fallida postoperación de Norwood en pacientes con síndrome de hipoplasia de ventrículo izquierdo

Abstract: En pacientes con Síndrome de Hipoplasia de Ventrículo Izquierdo (SHVI) la primera etapa hacia una fisiología univentricular de Fontan es la operación de Norwood, cuya mortalidad es 10-30%. En estos pacientes la extubación fallida se presenta en un 18% y se ha asociado a aumento de la mortalidad.Objetivo: Describir la frecuencia de extubación fallida y sus factores de riesgo en pacientes con SHVI operados (Norwood).Pacientes y Método: Estudio de casos y controles que incluyó a todos los pacientes con SHVI manej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…These results align with Herrera et al (3). They found that use of CPAP or BiPAP after extubation was associated with increased rates of extubation failure relative to HFNC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results align with Herrera et al (3). They found that use of CPAP or BiPAP after extubation was associated with increased rates of extubation failure relative to HFNC.…”
Section: Discussionsupporting
confidence: 93%
“…A higher rate of extubation failure was observed when patients were extubated to CPAP/BiPAP relative to patients who were extubated to either HFNC or NC (16% vs 7.8%). These results align with Herrera et al (3). They found that use of CPAP or BiPAP after extubation was associated with increased rates of extubation failure relative to HFNC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Failed extubation is associated with increased length of stay and increased risk of inpatient mortality (10)(11)(12)15). Extubation failure is most frequently de ned in published data as needing reintubation within 24 or 48 hours (16-18).…”
Section: Discussionmentioning
confidence: 99%
“…This interdependence between the pulmonary and systemic circulations leaves these patients at increased risk for inadequate systemic oxygen delivery and cardio-respiratory deterioration. (6-8) Thus, hemodynamic changes with intubation and extubation may be exaggerated in those with parallel circulation; therefore, patients with parallel circulation are at risk of extubation failure, an event associated with increased morbidity and mortality (10)(11)(12). Limited data describe the physiologic pro le associated with extubation failure, especially for children with congenital heart disease, including patients with parallel circulation.…”
Section: Introductionmentioning
confidence: 99%